TINGKAT SPIRITUALITAS DAN TINGKAT DEPRESI PADA LANSIA - Rahmah, Mutia; Husairi, Ahmad; Muttaqien, Fauzan (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2015)
Physical, psychological, and social changes in elderly can be a stressor in their lives that may lead todepression. Spirituality could be used as an adaptive coping source with the result that preventdepression. This study was aimed to know the relationship ofspirituality level with depression level inelderly at Panti Sosial Tresna Werdha (PSTW) Budi Sejahtera Province of South Kalimantan. Thestudy was a descriptive analytic with cross sectional approach. It was conducted at PSTW BudiSejahtera Province of South Kalimantan. There were 54 elderly as respondents were determined bypurposive sampling technique. The data were collected by using questionnaires of The DailySpiritual Experience Scale and the Short Form-Geriatric Depression Scale. Data analysis usedGamma Somers’d test. The result of this study showed that there was moderate negativelyrelationship of spirituality level with depression level in elderly at PSTW Budi Sejahtera Province ofSouth Kalimantan (p = 0.032, p < 0.05, r = -0,333). It was concluded that there was relationship ofspirituality level with depression level in elderly at PSTW Budi Sejahtera Province of SouthKalimantan.